Preparedness for hospital discharge and prediction of readmission. Issue 9 (29th February 2016) - Mixon, Amanda S.; Goggins, Kathryn; Bell, Susan P.; Vasilevskis, Eduard E.; Nwosu, Samuel; Schildcrout, Jonathan S.; Kripalani, Sunil
Abstract : BACKGROUND, OBJECTIVE: Patients' self‐reported preparedness for discharge has been shown to predict readmission. It is unclear what differences exist in the predictive abilities of 2 available discharge preparedness measures. To address this gap, we conducted a comparison of these measures. DESIGN, SETTING, PATIENTS: Adults hospitalized for cardiovascular diagnoses were enrolled in a prospective cohort. MEASUREMENTS: Two patient‐reported preparedness measures assessed during postdischarge calls: the 11‐item Brief Prescriptions, Ready to re‐enter community, Education, Placement, Assurance of safety, Realistic expectations, Empowerment, Directed to appropriate services (B‐PREPARED) and the 3‐item Care Transitions Measure (CTM‐3). Cox proportional hazard models analyzed the relationship between preparedness and time to first readmission or death at 30 and 90 days, adjusted for readmission risk using the administrative database‐derived Length of stay, Acuity, Comorbidity, and Emergency department use (LACE) index and other covariates. RESULTS: Median preparedness scores were: B‐PREPARED 21 (interquartile range [IQR] 18–22) and CTM‐3 77.8 (IQR 66.7–100). In individual Cox models, a 4‐point increase in B‐PREPARED score was associated with a 16% decrease in time to readmission or death at 30 and 90 days. A 10‐point increase in CTM‐3 score was not associated with readmission or death at 30 days, but was associated with a 6% decrease in readmission or death at 90 days. In models with both preparedness scores, B‐PREPARED retained an association with readmission or death at both 30 and 90 days. However, neither preparedness score was as strong a predictor as the LACE index when all were included in the model predicting 30‐ and 90‐day readmission or death. CONCLUSION: The B‐PREPARED score was more strongly associated with readmission or death than the more widely adopted CTM‐3, but neither predicted readmission as well as the LACE index. Journal of Hospital Medicine 2016;11:603–609. © 2016 Society of Hospital Medicine